Oxford Probability & Statistics - Nicholson, James; Series Editor, Rayner, David (Oxford Oxford University Press, 2000)
This stretching course builds the advanced skills students will need for the latest Cambridge assessments and prepares them for the transition to higher education. Engaging, real world examples are included throughout, making mathematics relevant to real life.
Include Color Illustrations
Keywords: Mathematical Statistics